Resonant tunneling diode photodetectors for optical communications. Issue 4 (16th January 2019) - Watson, Scott; Zhang, Weikang; Tavares, Joana; Figueiredo, Jose; Cantu, Horacio; Wang, Jue; Wasige, Edward; Salgado, Henrique; Pessoa, Luis; Kelly, Anthony
Abstract: Optical modulation characteristics of resonant tunneling diode photodetectors (RTD‐PD) are investigated. Intensity modulated light excites the RTD‐PDs to conduct data experiments. Simple and complex data patterns are used with results showing data rates up to 80 and 200 Mbit/s, respectively. This is the first demonstration of complex modulation using resonant tunneling diodes.